Determinants of farmers’ choice of land management strategies to climate change in drought prone areas of Amhara Region: The case of Lay Gayint Woreda, Northwest Ethiopia - Workie Mesfin Wale; Melak Abebe Tegegne; Menberu Teshome Zeleke; Mulualem Asfaw Ejegu; Endalkachew Sisay Yegizaw (Journal of Degraded and Mining Lands Management, 2021)
Climate change is one of the life-threatening challenges that face the ecosphere in recent decades. Climate change exacerbates the rate and magnitude of several ongoing land degradation processes. The impact is particularly high in unindustrialized states like Ethiopia. In recognition of the impact adaptation become the policy options to minimize the adverse effects of climate change. The main objective of this research paper is to analyze the determinants of farmers’ choice of land management approaches to climate change in drought prone areas of Amhara region: the case of Lay Gayint woreda, Northwestern Ethiopia. The study employed a multistage stratified sampling procedure (purposive and simple random). Data were obtained from 232 sample households. Primary data were collected from households via questionnaires, interview and focus group discussion. The households’ land management strategies to climate change were summarized by using percentage. Binary logistic regression model was also applied to analyze the factors that influence farmers’ choice of land management strategies. The farming households of the study area have attempted to give response to the impacts of climate change; but their capacity to adapt is challenged by a number of factors. Model results indicate that, Agro ecological setting and non-farm activities are found to be the most statistically significant determinants in the adoption of land management strategies. Solving financial problems, improving extension service, providing timely information and establishing early warning system, livelihood diversification and integrated watershed management practice would enable to increase the adaptive capacity of farmers